1982
DOI: 10.1113/jphysiol.1982.sp014127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular potassium accumulation and sodium pump activation on automatic canine Purkinje fibres

Abstract: SUMMARY1. Double barrel potassium-sensitive micro-electrodes were used to measure fluctuations in extracellular potassium ion concentration in large automatic canine Purkinje fibres.2. Slow accumulations of potassium were seen in the extracellular space during prolonged beating. Following cessation of prolonged beating, a depletion of extracellular potassium ions was noted.3. The time course of these slow changes in extracellular potassium concentration were shown to be a function of the diffusion properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
30
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 40 publications
8
30
0
1
Order By: Relevance
“…In the present experiments, it has been shown that immediately after the onset of repetitive stimulation, extracellular K+ activity starts to increase, reaches the maximal level within 30 s, and then declines toward the prestimulation levels during the period of stimulation, and after cessation of stimulation aK temporarily decreases below the level of bathing solution, gradually returning to the prestimulation levels. The results were qualitatively similar to those reported for other cardiac tissues by previous authors MORAD, 1976, 1978;KUNZE, 1977;KLINE et al, 1980;BROWNING and STRAUSS, 1981 ;KLINE and KUPERSMITH, 1982). The magnitude of the initial increase in aK was dependent on the frequency of stimulation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the present experiments, it has been shown that immediately after the onset of repetitive stimulation, extracellular K+ activity starts to increase, reaches the maximal level within 30 s, and then declines toward the prestimulation levels during the period of stimulation, and after cessation of stimulation aK temporarily decreases below the level of bathing solution, gradually returning to the prestimulation levels. The results were qualitatively similar to those reported for other cardiac tissues by previous authors MORAD, 1976, 1978;KUNZE, 1977;KLINE et al, 1980;BROWNING and STRAUSS, 1981 ;KLINE and KUPERSMITH, 1982). The magnitude of the initial increase in aK was dependent on the frequency of stimulation.…”
Section: Discussionsupporting
confidence: 81%
“…It is generally accepted that the hyperpolarization during and after prolonged trains of rapid stimulation has been attributed largely to electrogenic sodium pumping (VASSALLE, 1970;GADSBY and CRANEFIELD, 1979;KLINE et al, 1980;BOYETT and FEDIDA, 1981;KODAMA et al, 1981;COHEN et al, 1982;GADSBY and CRANEFIELD, 1982;GLITSCH, 1982;KLINE and KUPERSMITH, 1982;ELLIS, 1985), activated by a large rise of aNa (CoHEN et al, 1982;ELLIS, 1985). However, since the membrane potential of the cardiac tissue is influenced by the external potassium concentration as well as electrogenic Na-pumping activity, any changes in potassium distribution must be taken into consideration in evaluating changes in membrane potential.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical alternans has been attributed both to alternation in extracellular potassium levels at the start of each action potential (Kline & Kupersmith, 1980), and to incomplete membrane recovery between alternate beats (Hauswirth et al 1972;Boyett & Jewell, 1978). A second, more persistent type of alternans has been identified in the isolated preparation, probably linked to intracellular calcium cycling, and calcium entry into the cell during the action potential (Hirata et al 1980).…”
Section: Possible Mechanisms Of Ischaemic Alternansmentioning
confidence: 99%
“…Subsequently the contribution of electrogenic transport to the transmembrane potential was pursued (Gadsby and Cranefield, 1979;Falk and Cohen, 1984); at the same time the influence of rapid voltage-activated current fluxes on the transmembrane ionic balance was considered (Atwell et al, 1979;Kootsey et ai., 1980;Levis et al, 1983). Thus, intracellular sodium and calcium loading (Eisner et al, 1981a;Sheu and Fozzard, 1982;Ellis, 1985;Boyett et al, 1987) and extracellular potassium accumulation and depletion (Cohen and Kline, 1982;Kline and Kupersmith, 1982) were seen as routine consequences of repeated activation of transient transmembrane currents. Subsequent attempts (Deitmer and Ellis, 1980;Ellis and MacLeod, 1985;Piwnica-Worms et al, 1985) to include the role of both single ion and coupled transport systems (electrogenic and nonelectrogenic) analyzed in some detail the interaction of these multiple active and passive transport systems, showing, for example, that ions could be effectively coupled by sharing common cotransport partners even when not actually transported by the same molecular entity (Jacob et al, 1984).…”
Section: Introductionmentioning
confidence: 99%